MZI를 이용한 전광 직렬-병렬 데이터 형식 변환기 구현과 활용 방안 - 이성철; Lee, Sung Chul ((사)디지털산업정보학회 논문지, 7(2), 2011)
All-optical signal processing is expected to offer advantages in speed and power consumption against over electronics signal processing. It has a potential to solve the bottleneck issues of ultra-high speed communication network nodes. All-optical serial-to-parallel and parallel-to-serial data converters would make it possible to easily process the serial data information of a high-speed optical packet without optical-to-electronic-to-optical data conversion. In this paper, we explain the principle of simple and easily expandable all-optical serial-to-parallel and parallel-to-serial data converters based on Mach-Zehnder interferometers. We experimentally demonstrate these data converters at 10Gbit/s serial data rate. They are useful all-optical devices for the all-optical implementations of label decoding, self-routing, control of variable packets, bit-wise logical operation, and data format conversion.